Implementation Of Entrepreneurial Leadership Civil State Apparatus In The New Normal Era - Sa’diyah, Lukluk Hidayatus; Setiadi, Pompong B.; Rahayu, Sri (Best Journal of Administration and Management, 2022)
The Covid-19 pandemic has changed the fabric of the world community. The public is encouraged and even forced to stay at home to prevent the spread of the corona virus outbreak. These changes have a broad impact in various sectors, be it education, tourism, trade, and public services. The old and identical way of working face-to-face is no longer relevant to policies in the new normal era. The impact caused by the Covid-19 pandemic provides challenges as well as opportunities for the government to create competent and competitive civil servants in the new normal era. Increasing competence in terms of digital technology is a must for the current State Civil Apparatus in line with the urgency of implementing e-government in providing optimal public services to the community. The government in this case as the public service actor is required to formulate new policies related to the implementation of work in this new normal era. The application of entrepreneurial leadership has begun to be carried out in the leadership of the Civil Service Apparatus as one of the strategies to deal with changes in the new normal era.The research was conducted with a qualitative approach using a literature study. The conclusion obtained is that the application of entrepreneurial leadership in the Civil Service Apparatus is deemed necessary and needed in the public service sector in order to provide innovation and excel in providing optimal services to the community.